Analisis Kesiapan Mahasiswa dalam Mengikuti Pembelajaran Sistem Hibrid - Endra Ubaidillah; Dedi Prestiadi; Maulana Amirul Adha; Sasi Maulina; Aulia Nur Firdausi; Yunita Erviana; Nova Syafira Ariyanti (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2022)
Abstract: This study aims to identify the factors of student readiness in participating in hybrid system learning. A quantitative approach, with an explanatory design, was used to answer the aforementioned research objectives. The population in this study were students of the Faculty of Education, Universitas Negeri Malang, with a total sample of 346 students, which were analyzed using descriptive analysis. Based on the results of the study, the factors studied, namely health conditions showed a tendency at the level of good criteria, understanding of the implementation of hybrid learning was in the criteria of understanding, the lifestyle of the majority of students living in boarding houses/rented and mobility using private vehicles during college, the application of health protocols was on the frequent criteria, students' perceptions of hybrid lectures are good, parental support shows a supportive tendency, and students' readiness to take hybrid lectures is on the supportive criteria.Keywords: Hybrid learning; higher education; student readiness; Covid-19Abstrak: Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor kesiapan mahasiswa dalam mengikuti pembelajaran sistem hibrid. Pendekatan kuantitatif, dengan explanatory design, digunakan untuk menjawab tujuan penelitian yang telah disebutkan. Populasi dalam penelitian ini adalah mahasiswa Fakultas Ilmu Pendidikan, Universitas Negeri Malang, dengan jumlah sampel sebanyak 346 mahasiswa, yang dianalisis menggunakan analisis deskriptif. Berdasarkan hasil penelitian menunjukkan faktor-faktor yang diteliti yakni kondisi kesehatan menunjukkan kecenderungan pada tingkat kriteria baik, pemahaman pelaksanaan hybrid learning berada pada kriteria paham, gaya hidup mahasiswa mayoritas bertempat tinggal di kos/kontrakan dan mobilitas menggunakan kendaraan pribadi selama berkuliah, penerapan protokol kesehatan berada pada kriteria sering, persepsi mahasiswa terhadap perkuliahan hybrid baik, dukungan orang tua menunjukkan kecenderungan mendukung, dan kesiapan mahasiswa mengikuti perkuliahan hybrid berada pada kriteria mendukung.Kata kunci: Hybrid learning; perguruan tinggi; kesiapan mahasiswa; Covid-19